2014
DOI: 10.3928/01913913-20140513-02
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Choroidal Abnormalities in Pediatric Patients With Neurofibromatosis Type 1

Abstract: Choroidal abnormalities are frequent in neurofibromatosis type 1. Choroidal abnormalities detected by infrared reflectance imaging with optical coherence tomography can be used to diagnose neurofibromatosis type 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 16 publications
4
28
0
2
Order By: Relevance
“…As described by Goktas et al. () and Viola et al. (), choroidal nodules appear in healthy subjects as well, in 5% and 8%, respectively.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…As described by Goktas et al. () and Viola et al. (), choroidal nodules appear in healthy subjects as well, in 5% and 8%, respectively.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, Goktas et al. () observed choroidal abnormalities in 15 (78.9%) of 19 patients with NF1 and 1 (5%) of 20 control subjects.…”
Section: Introductionmentioning
confidence: 95%
“…This is comparable with previous studies in the literature with reported frequencies between 78.9% and 100% 7 8 13. No similar choroidal lesions were seen in the control subjects.…”
Section: Discussionsupporting
confidence: 92%
“…Choroidal nodules were recently found to be very specific for NF1, with a diagnostic accuracy of 90% if more than one nodule is present [3]. In NF1 children, choroidal nodules are seen in 71% (<12 years) to 78% (<16 years) [3, 4]. Therefore, choroidal nodules have been proposed to be added to the clinical diagnostic criteria for NF1 [3].…”
Section: Introductionmentioning
confidence: 99%